2018
DOI: 10.1093/geroni/igy024
|View full text |Cite
|
Sign up to set email alerts
|

From a Bird’s Eye View: Whole Social Networks in Adult Day Care Centers and Continuing Care Retirement Communities

Abstract: Background and ObjectivesThe present study describes whole social networks in 4 adult day care centers (ADCCs) and 4 continuing care retirement communities (CCRCs) in Israel.MethodEach respondent received a list of names of all individuals receiving services in the respective ADCC or CCRC and was asked to indicate whom he/she knows from the list. We derived whole social network properties and used hierarchical cluster analysis to group network settings. We further examined the ability of the social network dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Expansion of social engagement: This route points to the potential of the process to allow the participants to experience themselves as relevant and important to others and to relate to community roles such as a “friend,” “neighbor,” or “partner.” The ability to improvise and perceive the other with empathic attunement seems to enhance the participants’ sense of connectedness and engagement within the group. For people who facing the loneliness and social losses that are common in late life and particularly in the ADC community [ 100 , 101 ], the expansion of such social roles in the group contributes to promoting a positive view of the self and others [ 102 , 103 ]. Indeed, the intimate and shared atmosphere seems to have expanded to include the larger surrounding environment in the ADC community and in the participants’ families.…”
Section: Discussionmentioning
confidence: 99%
“…Expansion of social engagement: This route points to the potential of the process to allow the participants to experience themselves as relevant and important to others and to relate to community roles such as a “friend,” “neighbor,” or “partner.” The ability to improvise and perceive the other with empathic attunement seems to enhance the participants’ sense of connectedness and engagement within the group. For people who facing the loneliness and social losses that are common in late life and particularly in the ADC community [ 100 , 101 ], the expansion of such social roles in the group contributes to promoting a positive view of the self and others [ 102 , 103 ]. Indeed, the intimate and shared atmosphere seems to have expanded to include the larger surrounding environment in the ADC community and in the participants’ families.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the characteristics of our sample, many of our participants were sick, died, or transitioned outside the long‐term care setting over the 1‐year period of this study. Nonetheless, this study pays attention to a neglected topic that has received little attention, thus far, namely, older adults’ SCB in long‐term care institutions that are specifically geared to enhance or replace one's original local community of residence (Ayalon et al, ). As expected, our findings show that the social network plays a role in people's SCB.…”
Section: Discussionmentioning
confidence: 99%
“…That study concluded that ADCCs are therefore, ineffective in alleviating loneliness (Iecovich & Biderman, ). A different study comparing loneliness in ADCCs and CCRCs has found higher levels of loneliness (Ayalon, ), as well as sparser networks and lower social reciprocity in ADCCs (Ayalon, Yahav, & Lesser, ). CCRC residents on the contrary, have generally reported substantial social benefits associated with their relocation into the CCRC (Ayalon & Greed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, MJ had 89 residents living in a five-story building. Other information about the specific characteristics of the four CCRCs can be found in a previous publication based on these data [14].…”
Section: Design and Methodsmentioning
confidence: 99%
“…Following relocation to a CCRC, older adults tend to report a reduction in loneliness and an improvement in their social ties with residents and friends [12, 13]. Although researchers have argued that the number of ties between individuals who make up the social network in CCRCs is quite sparse, with most residents not even knowing each other [14], others have shown that the CCRC is effective in alleviating loneliness and facilitating social connections among its residents [15, 16]. However, some research has stressed the presence of cliques, conflicts, and loneliness in residential care settings [17, 18].…”
Section: Introductionmentioning
confidence: 99%